“Stella is not here”: Sidney’s acts of writing as acts of erasing - Christine Sukic (Etudes Epistémè, 2012)
In the Astrophil and Stella, Sidney stresses the concrete dimension of poetic composition and often alludes to concrete acts of writing by referring to the material objects of an actual inscription: ink, pen, paper, engraved stone, letters, the action of writing itself (write, engrave, imprint…), but also words and characters on the page. These references to the act of writing seem to point to a strong sense of authoriality on Sidney’s part. However, the act of writing in Astrophil and Stella is also questioned, first, by its very subject matter — a distant, inaccessible Petrarchan lover who turns out to be a mere word on the page, an absent presence — and then, by the frequent erasure of the words on the page as the poet is actually writing them. At the same time the poet is using self-reflexive devices, he is also claiming his impossibility to write. Sidney asserts his authorial identity as a poet through these contradictory acts of writing in Astrophil and Stella, and is in fact, like his contemporary Montaigne, “himself the matter of his book”. Even though, like many of his European contemporaries, he writes love poetry that imitates Petrarchan sonnets, and that supposedly places the woman at the centre of his poetry, it seems that the poet himself becomes the centre of his own poetry while Stella is erased from the page.